Responses of Soil Fungal Communities to Lime Application in Wheat Fields in the Pacific Northwest - Yin, Chuntao; Schlatter, Daniel C.; Kroese, Duncan R.; Paulitz, Timothy C.; Hagerty, Christina H. (Frontiers in Microbiology, 2021)
Liming is an effective agricultural practice and broadly used to ameliorate soil acidification in agricultural ecosystems. Our understanding of the impacts of lime application on soil fungal community is scarce. In this study, we explored the responses of fungal communities to liming at two locations with decreasing soil pH in Oregon in the Pacific Northwest using high-throughput sequencing (Illumina MiSeq). Our results revealed that the location, soil depth and liming did not significantly affect soil fungal diversity and richness. In contrast, location and soil depth had a strong effect on the structure and composition of soil fungal communities, whereas the impact of liming was much smaller, and location- and depth- dependent. Interestingly, families Lasiosphaeriaceae, Piskurozymaceae, and Sordariaceae predominated in the surface soil (0-7.5 cm) and were positively correlated with soil OM and aluminum, and negatively with pH. The family Kickxellaceae predominated in deeper soil (15-22.5 cm) had an opposite response to soil OM, aluminum, and pH. Furthermore, some taxa in Ascomycota, such as Hypocreales, Peziza and Penicillium, were increased by liming at one of the locations (Moro). In conclusion, these findings suggest that fungal community structure and composition rather than fungal diversity responded to location, soil depth and liming. Compared to liming, location and depth had a stronger effect on fungal communities, but some specific fungal taxa shifted with lime application.